Dynamical Modeling and Gait Optimization of a 2-D Modular Snake Robot in a Confined Space. Issue 2 (2020) - Classens, K.H.J.; Koopaee, M.A.J.; Pretty, C.; Weiland, S.; Chen, X.
Abstract: A model-based optimal gait is obtained for the 2-D locomotion of a modular snake robot in a duct. Optimality is considered in the sense of traveling as fast as possible or traveling with minimal energy consumption. The novelty of the work lies in the development of a framework to cast the full dynamic behavior, including contact constraints with simple objects, into an optimization problem which allows for gait parameter, control parameter and/or physical parameter optimization. Optimal gait and control parameters are found via a surrogate optimization procedure which reveals optimal locomotion strategies depending on the duct width and optimization criteria. The framework is tested and illustrated with a number of optimizations of 2-D locomotion of a snake robot where either traveling time or energy consumption is minimized.